Ultrasonography Profiles in Patients with Asymptomatic Hyperuricemia - Awalia; Yeheskiel, Tigor; Setiawati, Rosy; Rahardjo, Paulus; Triasti Putri, Arinditia (Gaceta Médica de Caracas, 2023)
Backgrounds: Asymptomatic hyperuricemia (AHU) patients mostly do not develop gouty arthritis. The best procedure to investigate whether they have MSU deposition has not been established. We report our preliminary study about ultrasonography on AHU patients. Methods: In this cross-sectional study, we enrolled asymptomatic hyperuricemia patients who matched the gout classification criteria of the American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) (2015). Six joints were examined per patient by ultrasonography including the first metacarpophalangeal (MCP) joints, first metatarsophalangeal (MTP) joints, and trochlear knees to determine pathological findings which may demonstrate clinically silent urate deposits in asymptomatic hyperuricemia individuals.